2024
DOI: 10.1029/2023gl106867
|View full text |Cite
|
Sign up to set email alerts
|

Fast Tearing Mode Driven by Demagnetized Electrons

Olga O. Tsareva,
Makar V. Leonenko,
Elena E. Grigorenko
et al.

Abstract: Recent MMS observations have discovered electron‐scale super‐thin current sheets (STCSs) with a partial electron demagnetization, which distinguishes them from the ion‐scale TCSs traditionally observed by the Cluster mission. Our investigation focuses on the dynamics of STCSs and reveals new aspects influencing their stability. We use the earlier proposed 1D collisionless self‐consistent equilibrium STCS model and show that the free parameters of this model, such as the relative part of demagnetized electrons,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…The increase in abundance of unmagnetized electrons may trigger the development of fast electron tearing mode and the ECS decay. Recently Tsareva et al (2024) investigated the stability of 1D collisionless self-consistent equilibrium of the STCS generated by the population of demagnetized electrons. They showed that the increase in relative abundance of demagnetized electrons can contribute to the development of electron tearing instability, which is an order of magnitude faster and has shorter wavelengths than the ion tearing modes in ion-scale thin current sheets.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in abundance of unmagnetized electrons may trigger the development of fast electron tearing mode and the ECS decay. Recently Tsareva et al (2024) investigated the stability of 1D collisionless self-consistent equilibrium of the STCS generated by the population of demagnetized electrons. They showed that the increase in relative abundance of demagnetized electrons can contribute to the development of electron tearing instability, which is an order of magnitude faster and has shorter wavelengths than the ion tearing modes in ion-scale thin current sheets.…”
Section: Discussionmentioning
confidence: 99%
“…They found that this phase was controlled by electron kinetic only, while after the onset, reconnection proceeds to the "standard" stage controlled by ion kinetics. Tsareva et al (2024) discussed the MMS observations of the ECS evolution inside a magnetic island transported by the fast bulk flow. The ECS was formed by stringly accelerated field-aligned electron beam.…”
Section: Discussionmentioning
confidence: 99%